Malaria among foreign workers in Selangor, Malaysia - Mohamed, Masitah; Nor Aini, M.N.; Said, Mas Ayu (Faculty of Medicine, University of Malaya, 2008)
The state of Selangor, Malaysia, is facing a significant rise in the number of malaria cases with the incidence varying from 20 to 90 per 100,000 persons in a population. A study was carried out to describe the distribution of malaria cases in relation to the growing number of foreign workers in Selangor. Data were reviewed using the return forms 'PBV (M) 101', a summary of malaria cases in Selangor for 2006 and Annual Reports of Vector-Borne Disease Control Unit, Selangor State Department for 2001- 2005. The malaria cases in Selangor varied between 172 cases in 2001 and 90 cases in 2006. Most of the cases were contributed by foreign workers, who were predominantly male of economically active age group and came from malaria endemic countries. Most of these cases were concentrated in the urban districts. Malaria is still endemic in Selangor. Malarial infection has the potential of contributing to an urban outbreak of malaria.